Model Keamanan Bersama Antara TNI Al, Polri dan Bakamla Untuk Menjaga Perekonomian di Perbatasan Laut Indonesia Malaysia - Handoyo, Wuri; Adiwijaya, Achmad Jaka Santos; Nurwati, Nurwati (Syntax Corporation, 2025)
The security of the Indonesia-Malaysia maritime border by the Indonesian Navy, the Indonesian National Police, and Bakamla faces various problems that impact the economy. These problems include a lack of inter-agency coordination, differences in mandates and operational cultures, and challenges in law enforcement. Some of these problems include the Indonesian Navy, the Indonesian National Police, and Bakamla having different duties and authorities, but often operating in the same area. This lack of coordination and effective communication can lead to overlapping or even clashes in the execution of duties, ultimately reducing security effectiveness. The objectives of this study include: to identify and analyze the institutional regulatory aspects of the Indonesian Navy, the Indonesian National Police, and Bakamla in safeguarding the economy on the current Indonesia-Malaysia maritime border. To identify and analyze the policy framework and joint security model between the Indonesian Navy, the Indonesian National Police, and Bakamla to safeguard the economy on the Indonesia-Malaysia maritime border. The research method used is a normative juridical research method, namely law is conceptualized as norms, rules, principles or dogmas. The results of the study revealed that the institutional regulatory aspects between the Indonesian Navy, the Indonesian National Police, and Bakamla to maintain the economy on the Indonesian-Malaysian maritime border currently involve a harmonious division of roles, where the Indonesian Navy focuses on defense and maintaining state sovereignty, the Indonesian National Police is tasked with maintaining public security and order, while Bakamla is specifically tasked with security patrols and law enforcement at sea. Existing regulations underlie clear collaboration to prevent economic threats such as illegal fishing and smuggling. The conclusion of the study shows that the policy framework and security model between the Indonesian Navy, the Indonesian National Police, and Bakamla to maintain the economy on the Indonesian-Malaysian maritime border is a synergistic and integrated division of roles to maintain sovereignty and the economy. The Indonesian Navy focuses on maritime defense and sovereignty of maritime areas, the Indonesian National Police is tasked with law enforcement and maintaining civil order in the waters, while Bakamla acts as a coordinator and law enforcer in Indonesian maritime areas, including the borders. This model is an application of a universal national defense system, where these three institutions work together in an integrated, directed, and sustainable manner.